Closing the Gap between Vocational and General Education? Evidence from University Technical Colleges in England - Steve Machin; Sandra McNally; Camille Terrier; Guglielmo Ventura (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Some countries, notably those which have long had a weak history of vocational education like the UK and the US, have recently seen a rapid expansion of hybrid schools which provide both general and vocational education. England introduced `University Technical Colleges' (UTCs) in 2010 for students aged 14 to 18. 49 UTCs have been created since then. We use a spatial instrumental variable approach based on geographical availability to evaluate the causal effect of attending a UTC on student academic and vocational achievement and on their labour market outcomes. For those pupils who enter the UTC at a non-standard transition age of 14, UTCs dramatically reduce their academic achievement on national exams at age 16. However, for students who enter at a more conventional transition age of 16, UTCs boost vocational achievement without harming academic achievement. They also improve achievement in STEM qualifications, and enrolment in apprenticeships. By age 19, UTC students are less likely to be unemployed and more likely to study STEM at university.
Keywords: I20; I21; I28; 330; technical education; tracking; school value-added